2016
DOI: 10.1186/s40711-016-0042-1
|View full text |Cite
|
Sign up to set email alerts
|

Children born in July and August: a study on the age regulation in primary school and student’s education access and development

Abstract: This paper discusses at the microlevel the educational inequality resulting from the cutoff birthdate regulation in the current primary school admission system. According to our research, among the students who enroll in school, students born in July and August display a relative disadvantage and adaptive difficulties in the construction of self-identity and study ability when compared with those born in September and October. Students born between November and June in the following year have mid-level perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…They found that high school students born in July and August, being the youngest students given the enrollment cutoff date in August, had more academic problems, lower levels of self-confidence, and greater likelihood of being addicted to internet games. As a result, July-August-born students were found to be less likely to be admitted to key high schools when compared to September-October-born students, the oldest group at the time of initial school entry, having been born in the months immediately after the cutoff date (Liu and Li 2015).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…They found that high school students born in July and August, being the youngest students given the enrollment cutoff date in August, had more academic problems, lower levels of self-confidence, and greater likelihood of being addicted to internet games. As a result, July-August-born students were found to be less likely to be admitted to key high schools when compared to September-October-born students, the oldest group at the time of initial school entry, having been born in the months immediately after the cutoff date (Liu and Li 2015).…”
Section: Introductionmentioning
confidence: 98%
“…The exact enrollment cutoff date, however, is somewhat arbitrarily chosen, imposing uniform school-entry timing even when young children of the same age may vary in school readiness, leading to academic advantages or disadvantages for children born in different months (Bedard and Dhuey 2006;Dhuey and Lipscomb 2010;McEwan and Shapiro 2008;Mühlenweg and Puhani 2010). In a recently published article entitled "Children Born in July and August: A Study on the Age Regulation of Primary School Admission and Student's Education Access and Development," Liu and Li (2015) reported how birth months, thought to be randomly distributed, affected the academic performances of adolescents due to the rule of minimum age and enrollment cutoff date specified by the Compulsory Education Law in China. They found that high school students born in July and August, being the youngest students given the enrollment cutoff date in August, had more academic problems, lower levels of self-confidence, and greater likelihood of being addicted to internet games.…”
Section: Introductionmentioning
confidence: 99%
“…The policy of grouping students born up to one year apart in the same class, based on an arbitrary cutoff date, is widespread in OECD countries but costly in terms of human capital formation. Indeed, scholars have shown that the youngest pupils in a class are more likely to suffer from grade retention, to be assigned to remedial classes, to receive lower grades, to be retained, and to skip lessons (Peña, 2016;Liu & Li, 2016;Navarro et al, 2015;Ponzo & Scoppa, 2014;Sprietsma, 2010;Elder & Lubotsky, 2009;Bedard & Dhuey, 2006). These performance gaps are also known as relative age effects (RAEs;Allen & Barnsley, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, lower performance may lead to low self-esteem, and thus to limiting communication with peers (Liu & Li, 2016;Thompson et al, 2004). Fifth, these adverse situations may cause depression, which is another factor commonly associated with loneliness and thus fewer social contacts (Matthews et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation